Microstructure and mechanical properties of iron-containing titanium metal-metal composites. (August 2020) - Lin, Fangrui; Chen, Zhixing; Liu, Bin; Liu, Yong; Zhou, Chengshang
Abstract: Titanium-based metal-metal composites show promises in many applications. In this work, iron-containing titanium-based composites were fabricated by using powder metallurgy method and rotary swaging process. Titanium-based composites with steel addition were sintered at temperature below TiFe eutectic temperature. Increase of the steel addition to 23% resulted in formation of TiFe intermetallic and density decrease in the composites. Further, the as-sintered composites present relatively good workability so hot rotary swaging of the as-sintered composites can be conducted. Steel particles were diffused into the Ti matrix and the composite transformed to a discontinuous β-Ti fiber-reinforced structure. As a result, mechanical properties (in axial direction) of the swaged composites were significantly improved. The tensile strength and elongation reached 1360 MPa and 9.3%, respectively. Highlights: A novel iron-containing titanium metal-metal composite was prepared by means of powder metallurgy and rotary swaging process. The composites have a heterogeneous structure with fibrous β-Ti reinforcement and α-Ti matrix. The tensile strength and elongation of the composite reached 1360 MPa and 9.3%, respectively.